Performance Analysis of Various Routing Protocols in 3D Body Architecture using Qualnet in WBSN - Deepak Sethi; Partha Pratim Bhattacharya (IPTEK The Journal for Technology and Science, 2018)
Wireless Body Sensor Network (WBSN) is a connectionless architecture used to monitor health of a patient or an athlete. Various routing strategies have been proposed to increase the network lifetime. In this work, we have compared some well known ad-hoc network routing protocols like DYMO, DSR, ZRP and LAR1 in WBSN. WBSN works in a small area like Bluetooth or Zigbee. Few gateway nodes are also considered to route the traffic. The simulations have been performed using Qualnet 6.1. Various parameters like jitter, throughput, end to end delay, packet delivery ratio has been used for comparison. Results revealed that ZRP have least end to end delay (0.2) and jitter (0.1), but have low throughput i.e. 2362 b/s as compared to DYMO and DSR i.e. 2752 b/s and 3026 b/s.